Influence of Induced Diabetes on the Severity of Experimental Toxoplasmosis in Mice (NTU Journal of Agriculture and Veterinary Science, 2025)
This study aimed to evaluate the effect of induced diabetes on the severity of experimental toxoplasmosis in mice. 10 placenta samples were collected from Al-Salam Hospital in the city of Mosul. The parasite isolated and identified. Eighty mice were experimental diabetes were induced with Alloxan, and divided into three groups; two groups 40 mice of both sexes (20 males and 20 females) infected in Toxoplasma gondii (T. gondii), and 20 mice consider as a control group. Mice were sacrificed at one, two, three and six weeks post infection (p.i.), blood serum was collected and evaluated for the severity of T. gondii infection using an ELISA kit, and glucose and insulin levels were measured. Tissue cysts in brain casts were also assessed. The results showed a significant difference at P < 0.01. in the glucose level in all groups, the highest glucose level was recorded at six week i.p in females which recorded 274.13±74.13. It was also observed that there is an increase in the rate of insulin level, the highest rate was showed in the second and sixth weeks p.i in male group which recorded16.15±4.14. furthermore, it was found that the highest concentration level forIGg was recorded at third week p.i females which recorded 0.52±0.06., Furthermore, a statistical relationship was found between males and females according to number of cysts.